A modified method to estimate chain inverse catenary profile in clay based on chain equation and chain yield envelope. (October 2017) - Han, Congcong; Liu, Jun
Highlights: A modified method to estimate the chain inverse catenary profile in soil was proposed. A testing arrangement that can be used to investigate the chain-soil-anchor interaction was designed. The yield envelopes for both chain and rope were proposed. Abstract: Offshore floating facilities are fixed by anchoring systems embedded in seabed soils through chains or ropes. The chain inverse catenary profile embedded in soils influences both the anchor failure mechanism and the anchor holding capacity. The chain mobilizes varying soil normal and tangential resistances during motion, hence it is with difficulty to depict the chain profile. The present work proposed a modified method to estimate the chain inverse catenary profile with high accuracy based on the chain equations and the chain yield envelope. A testing arrangement with three load cells and two MEMS (Micro-electromechanical systems) accelerometers included was designed in model tests. By model tests, the loading combinations of the soil tangential and normal resistances on the chain were obtained and the yield envelopes for both chain and rope were determined. In addition, supplemental model tests were performed to validate the modified method proposed in this study, and the testing results indicated that the estimated chain inverse catenary profile was in good agreement with the actual one. Moreover, the testing arrangement is beneficial in investigating the chain-soil-anchor interaction.